Trust Mediates The Factors That Influence Purchase Intention For Co-Branded Local Cosmetics - Fitri, Alissya Maidha; Lady, Lady (Universitas Muhammadiyah Jakarta, 2024)
In the pursuit of enlightenment, this scholarly investigation unfolded through the distribution of meticulously crafted questionnaires and rigorous data computation. Consequently, the yielded results transcend mere numbers, including quantitative and qualitative elements. This analytical inspection aims to uncover the deep implications of things such as brand awareness, social media marketing, brand image, e-WoM (electronic word of mouth), brand equity, and trust. These elements, seen as potential mediators, hold the potential to exert influence on the purchase intention of co-branded local cosmetics products. The data employed in this scholarly inquiry were gathered through the dissemination of questionnaires among consumers who had previously acquired Co-Branded local cosmetics within the confines of Batam City in Indonesia. The collected responses underwent meticulous analysis, facilitated by the technological prowess of SmartPLS. The distribution of the questionnaires was executed via Google Forms, skillfully designed to adhere to specific terms and conditions. The outreach strategy encompassed both online and offline channels, ensuring a comprehensive and diverse participant pool. In the contemporary landscape, research on local cosmetics has emerged as a popular and pertinent topic. Notwithstanding, prevailing studies in this domain have predominantly concentrated on generic cosmetic sales strategies. Consequently, a noticeable research gap exists. This prompted the conception of the present analysis, aimed at enriching our understanding of marketing dynamics achieved through collaborative efforts between distinct brands. The specific focus is on exploring the ramifications of co-branding and its intrinsic impact on purchase intention, thereby contributing valuable insights to the current body of knowledge in this domain.